1981
DOI: 10.1002/ana.410100510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dipropylacetate on brain development

Abstract: Dipropylacetate (DPA: valproic acid) is a new anticonvulsant reported to be effective in many types of seizures including those that occur early in life. This study describes the effects of chronic administration of DPA upon a developing organism. Four-day-old rat pups were injected daily with either 75 mg/kg DPA, 200 mg/kg DPA, or vehicle until day 18. Administration of DPA resulted in decreased body and organ weights, with the greatest reductions in the 200 mg/kg group. To control caloric intake, and additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Phenytoin can cause permanent damage to the cerebellum and occasionally a more in sidious encephalopathy [11], Phénobarbital can cause neuronal deficits and decrease body and brain weights [12,13], Valproate can cause a decrease of brain weight [9]. CZP is a new, potent antiepileptic drug, but infor mation regarding its effects on brain devel opment and cognitive function in children is not available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenytoin can cause permanent damage to the cerebellum and occasionally a more in sidious encephalopathy [11], Phénobarbital can cause neuronal deficits and decrease body and brain weights [12,13], Valproate can cause a decrease of brain weight [9]. CZP is a new, potent antiepileptic drug, but infor mation regarding its effects on brain devel opment and cognitive function in children is not available.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CZP did not cause significant effects on body weight, entire brain weight, or re gional brain weight. It is suggested that CZP has less effect on body and brain weights than phénobarbital, phenytoin, and val proate [9,12,13], However, an apparent trend towards decreased weight in all three measured parameters appeared in the highdose group. The high dosage (0.5 mg/kg/ day), when used for 16 days in mice (n = 35),…”
Section: Of Thementioning
confidence: 91%
See 1 more Smart Citation
“…Long Evans rats exposed during the early postnatal period (P6-P12) to valproate (150mg/kg) were found to have sensory-motor gating abnormalities and impairments in fine motor performance [17], while Sprague Dawley rats exposed exposed from P6-P18 to 150mg/kg of valproate showed deficits in the development of social play [18]. Relevant to neural development, P4-P18 rats exposed to 75–200mg/kg of valproate were found to have a significant decrease in brain weight [19] and rats exposed to three days of 50 to 400mg/kg of valproate between the ages of P3 and P30 were found to have increased apoptotic cell death throughout the brain, suggesting wide spread loss of cells [2022]. Together, these results provide compelling support for more in depth studies of the effects of valproate on postnatal brain development.…”
Section: Introductionmentioning
confidence: 99%
“…The main indication for its use is in treatment of absence seizures although it has been used in a variety of seizure disorders, often in combination with other anticonvulsants. Although VPA, as a carboxylic acid, is structurally unrelated to other kinds of anticonvulsant drugs, prenatal exposure to it, like other prenatal anticonvulsant exposures, has been associated with congenital malformations in laboratory animals [Brown et al, 1980;Kao et al, 1981: Diaz andShields, 1981;Bruckner et al, 1983;Paulson et al, 19851. VPA is known to cross the human placenta and is present in higher concentration in the infant than in the mother [Dickinson et al, 1979;Nau et al, 19811. Single case reports of birth defects occurring in offspring of women taking VPA during pregnancy have been published since 1980 suggesting that VPA might have teratogenic properties in humans as well [Dalens et al, 1980;Gomez, 1981;Thomas and Buchanan, 1981;Clay et al, 1981;Stanley andChambers, 1982: Bailey et al, 1983;Blaw and Woody, 1983;Bantz, 1984: Garden et al, 1985Tein and MacGregor, 19851.…”
mentioning
confidence: 99%